DIGITAL PROMOTION STRATEGY: UTILIZATION OF DIGITAL ADVERTISING, ENDORSEMENTS, AND SOCIAL MEDIA CAMPAIGNS AT JNC COOKIES - Jota Yovanto; Rini Puspita Dewi; Suci Fitriani; Luthfiani Chintia Wardani; Zia Dzilalul Haq; Revalsyah Alwi Alfarizky; Rizaldi Afrizafany; Ingrit Fatharani; Indah Permatasari; Oksa Putri Mulyadi; Yuyun Yuniarsih (PT. Jurnal Center Indonesia Publisher, 2026)
The increasing intensity of competition in the culinary business sector of Micro, Small, and Medium Enterprises (MSMEs), particularly in snack food products such as JNC Cookies, necessitates the implementation of effective digital promotion strategies to expand market reach and improve sales performance. Changes in consumer behavior that increasingly rely on digital platforms to obtain information, evaluate purchasing decisions, and interact with brands have made adaptation to digital marketing an unavoidable requirement. Therefore, this study aims to analyze the planning, implementation, and effectiveness of digital promotion strategies through the utilization of digital advertising (paid advertising), endorsements, and social media campaigns in enhancing brand awareness and consumers’ purchase intention toward JNC Cookies. This study employs a descriptive qualitative approach, with data collection techniques including in-depth interviews, observation of social media activities, and analysis of the performance of implemented digital marketing campaigns. In addition, several supporting indicators were measured, such as content reach, engagement rate, consumer interactions, and changes in sales volume during the campaign period. The collected data were subsequently analyzed to identify the relationship between digital promotional activities and consumer responses. The expected outcomes of this study include the formulation of an applicable digital promotion strategy model for food-sector MSMEs, recommendations for the development of sustainable social media campaigns, and the mapping of the roles of endorsements and digital advertising in strengthening the brand positioning of JNC Cookies. The findings of this study are expected to provide practical contributions for MSME practitioners in optimizing the use of digital media as an effective, measurable, and consumer-oriented promotional tool.